PRP8 Intein in Onygenales: Distribution and Phylogenetic Aspects - Garcia Garces, Hans [UNESP]; Hamae Yamauchi, Danielle [UNESP]; Theodoro, Raquel Cordeiro; Bagagli, Eduardo [UNESP] (Springer Nature, 2019)
Inteins (internal proteins) are mobile genetic elements, inserted in housekeeping proteins, with self-splicing properties. Some of these elements have been recently pointed out as modulators of genetic expression or protein function. Herein, we evaluated, in silico, the distribution and phylogenetic patterns of PRP8 intein among 93 fungal strains of the order Onygenales. PRP8 intein(s) are present in most of the species (45/49), mainly as full-length inteins (containing both the Splicing and the Homing Endonuclease domains), and must have transferred vertically in all lineages, since their phylogeny reflects the group phylogeny. While the distribution of PRP8 intein(s) varies among species of Onygenaceae family, being absent in Coccidioides spp. and present as full and mini-intein in other species, they are consistently observed as full-length inteins in all evaluated pathogenic species of the Arthrodermataceae and Ajellomycetaceae families. This conservative and massive PRP8 intein presence in Ajellomycetacean and Arthrodermatecean species reinforces the previous idea that such genetic elements do not decrease the fungal fitness significantly and even might play some role in the host–pathogen relationship, at least in these two fungal groups. We may better position the species Ophidiomyces ophiodiicola (with no intein) in the Onygenaceae family and Onygena corvina (with a full-length intein) as a basal member in the Arthrodermataceae family.
Keywords: Evolution; Onygenales; Phylogeny; PRP8 intein